2018
DOI: 10.14201/eks20181926381
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Primary School Children in Computational Thinking: Designing and Developing Videogames

Abstract: This paper presents the results of a project on Computational Thinking education for primary school pupils. During the project – called Computational Thinking for children education – 81 students from a primary school in Italy have been guided to the design and development of computer games through the Microsoft Kodu game development platform. Different activities have been proposed to the pupils with the aim of promoting Computational Thinking abilities and skills. A narrative approach has been adopted throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 19 publications
(16 reference statements)
1
2
0
2
Order By: Relevance
“…In fact, the result of the t-test comparing total scores on the Bebras tasks obtained by participants in the two groups showed a significantly higher performance in tasks solution in children attending the robotics laboratory. First of all, our findings are consistent with those reported by existing literature that confirmed the effectiveness of robotics education in supporting the acquisition of cognitive skills related to CT [19,20,36,37]. More specifically, findings of the present study are similar to those shown in a previous study evaluating the development of CT skills in a sample of fifth-grade students [38].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the result of the t-test comparing total scores on the Bebras tasks obtained by participants in the two groups showed a significantly higher performance in tasks solution in children attending the robotics laboratory. First of all, our findings are consistent with those reported by existing literature that confirmed the effectiveness of robotics education in supporting the acquisition of cognitive skills related to CT [19,20,36,37]. More specifically, findings of the present study are similar to those shown in a previous study evaluating the development of CT skills in a sample of fifth-grade students [38].…”
Section: Discussionsupporting
confidence: 92%
“…The use of video game engines involves students in the creation of the content on which they work, making them participants in the construction of knowledge and not just as mere consumers [37]. The emergence of simple programming languages that allow the creation of video games makes them easier to use for those interested who do not have advanced knowledge in this area, and has therefore made it possible to incorporate the creation of video games in classrooms from primary school onwards [38]. Some researchers use video game creation to motivate pre-university students to become interested in computer science [39].…”
Section: Use Of Video Game Engines In Educationmentioning
confidence: 99%
“…Three subjects are often involved in previous studies that have two types of learning. Research subjects frequently involved are pre-service elementary education teachers (García-Ceberino, Feu, Gamero, & Ibáñez, 2021;M Martín del Pozo, Basilotta Gómez-Pablos, & García-Valcárcel Muñoz-Repiso, 2017;Mee Mee et al, 2020;Perera & Hervás-Gómez, 2021), primary school teachers (Fraga-Varela, Vila-Couñago, & Rodríguez-Groba, 2021;Susman & Pavlin, 2020;Yaşar, Kıyıcı, & Karataş, 2020), and primary school children (Chiazzese, Fulantelli, Pipitone, & Taibi, 2018;Kayumova, Gainullina, Akhmadieva, Matvienko, & Kabakhidze, 2021). This learning is also related to mobile learning which is considered to be able to penetrate space and time (Jen- Yi, Chuan-His, & Yi-Hsin, 2020), and e-learning which is promoted to increase student motivation, engagement, and learning (T. Alshammari, 2020).…”
Section: Figure 8 the Main Fields Of Study That Use Games In Their Le...mentioning
confidence: 99%